Biblioteki Wydziału Prawa i Nauk Społeczno-Ekonomicznych KUL w okresie II Rzeczpospolitej - Nowakowska, Monika (Archiwa, Biblioteki i Muzea Kościelne, 2017)
During the interwar period at the Faculty of Law and Social-Economic Sciences of the Catholic University of Lublin, there were three main sectional libraries: legal, economic and social. In these libraries there were book collections, also referred to as libraries, assigned to a particular seminar. They were treated as research aid for employees and students. Initially, they were supervised by professors, who decided on the shape of the collection as well as the selection of library staff. Over time, there appeared a position of librarian who managed the collections of all the seminary libraries. In the 1930s librarians were assigned to each section separately; and they were responsible, among others, for cataloguing books and periodicals, making the collection available, providing research information, repairing damaged books, doing bookkeeping and arranging duty hours for scholarship holders. Seminar book collections increased as new books were bought and donated. The most important donations were books offered by the Main Library of the University of Lublin and Professor A. Szymański, a lecturer from the Faculty of Law and Social-Economic Sciences.